PENGARUH GOOD CORPORATE GOVERNANCE DAN RETURN ON ASSET TERHADAP NILAI PERUSAHAAN - Marina, Ade; Norisanti, Nor; Saori, Sopyan (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The purpose of this study was to determine the effect of the implementation of good corporate governance, return on assets on the value of companies in the consumer goods industry sector listed on the IDX 2019-2022 (Quarterly). The research methods used in this research are descriptive and associative methods with a quantitative approach. The population in this study are consumer goods industry sector companies listed on the IDX for the period 2019 to 2021 with the samples used in the study, namely 2 manufacturing companies in quarters with a total data of 32 financial statement periods from 2019 - 2022, namely PT GUDANG GARAM TBK and PT KINO INDONESIA TBK. The results of the research show that both Good Corporate Governance and Return On Assets do not have an individual significant influence on Company Value